Two DNA methyltransferases from murine erythroleukemia cells: purification, sequence specificity, and mode of interaction with DNA. - Bestor, T H (1983)
Dye-ligand chromatography on Cibacron blue F3GA-agarose has been used to resolve two species of DNA (cytosine-5-)-methyltransferase from nuclear extracts of uninduced Friend murine erythroleukemia cells. Each species has been highly purified; the activities in the first and second peaks were associated with polypeptides of Mr 150,000 and 175,000, respectively. Analysis of substrate specificity with synthetic DNAs and restriction fragments of phi X174 replicative form DNA and pBR322 DNA showed that neither enzyme had dependence on the sequence context of CpG dinucleotides; poly(dG-dC) had the greatest methyl-accepting activity of any unmethylated DNA substrate tested. De novo methylation by both enzymes was inefficient relative to methylation of hemimethylated sites. Methyl-accepting activity was strongly dependent on DNA chain length. This observation suggests that binding to DNA, followed by one-dimensional diffusion of enzyme along the DNA molecule, is important in the mechanism by which DNA methyltransferase locates its recognition sites.